Possibility of Reducing the Thermal Conductivity of Ceramic Refractory Materials - Watan, A. W. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The research work covers a study of the possibility of producing porous ceramic bodies as a thermal insulators by adding fired Dechla kaolinite (grog)to the same non burned kaolinite.Different weight percentage ranged between (0,15,25,35and40)from grog and sawdust passed through mesh 50 to Deuchla-clay kaolinit.Cylindrical shape samples (30mm diameter and 30mm height) were prepared by the semi-dry methed,moulding pressure was 50 N/mm2. After drying at 110oc,the samples were burnet in the furnace at temperatures 900,950,1000,1050,and 1100 oc. The sawdust burnt out and leaves air spaces which contribute to the high thermal insulation value.The fired samples were investigated to determine bulk density , porosity, compressive strength and the thermal conductivity .It was found that the increase of grog ratio produces a decrease in bulk density ,compressive strength and thermal conductivity, but addition of sawdust to the samples produces decrease greater than when addition the grog